Oral and Silent Reading and Its Effect on Reading Comprehension Levels of Grade 7 Students Under the MATATAG Curriculum - Dignos, Jayson; Mangindra, Anesa (International Journal of Arts, Sciences and Education, 2025)
This study aims to examine the reading levels of seventh-grade students, specifically in oral and silent reading, as well as their level of comprehension under the MATATAG Curriculum. It was conducted at Lagao National High School, General Santos City, during the third quarter of the 2024-2025 school year. The study used a quasi-experimental design, where the performance levels of 33 students in oral reading and 34 students in silent reading were assessed based on pre-test and post-tests. The test used was derived from the PHIL IRI to measure comprehension levels. The effectiveness of the prepared lesson plans was also evaluated in terms of content, appropriateness, and technical quality through expert validation. The study found that students in oral reading started at the instructional level and progressed to the independent level in the post-test. Meanwhile, in silent reading, most students were at a frustration level initially but showed a slight improvement in the post-test. Although there was no significant difference in the pre-test and post-tests in oral reading, a significant difference was found in silent reading. In terms of mean gain percentage, oral reading scored 5.18, while silent reading scored 8.39. Based on the findings, it was proven that supplemental instruction in both oral and silent reading is effective in improving comprehension levels. However, reading strategies need further enhancement to better support students, particularly those at the frustration level. In this regard, the implementation of remedial reading programs is recommended to improve students' reading skills.